Sex-specific differences in adverse outcome events among patients with atrial fibrillation. Issue 18 (8th February 2022) - Evers-Dörpfeld, Simone; Aeschbacher, Stefanie; Hennings, Elisa; Eken, Ceylan; Coslovsky, Michael; Rodondi, Nicolas; Beer, Jürg H; Moschovitis, Giorgio; Ammann, Peter; Kobza, Richard; Ceylan, Selinda; Krempke, Melina; et al.
Abstract : Objective: To assess whether women with atrial fibrillation (AF) have a higher risk of adverse events than men during long-term follow-up since controversial data have been published. Methods: In the context of two very similar observational multicentre cohort studies, we prospectively followed 3894 patients (28% women) with previously documented AF for a median of 4.02 (3.00–5.83) years. The primary outcome was a composite of ischaemic stroke, myocardial infarction and cardiovascular death. Secondary outcomes included the individual components of the composite outcome, hospitalisation for heart failure, major and clinically relevant non-major bleeding, stroke or systemic embolism and non-cardiovascular death. Results: Mean age was 73.1 years in women vs 70.8 years in men. The incidence of the primary endpoint in women versus men was 2.46 vs 3.24 per 100 patient-years, respectively (adjusted HR (aHR) 0.74, 95% CI 0.58 to 0.94; p=0.01). Women died less frequently from cardiovascular (aHR 0.57, 95% CI 0.41 to 0.78; p<0.001) and non-cardiovascular causes (aHR 0.68, 95% CI 0.47 to 0.98; p=0.04). There were no significant sex-specific differences in stroke (incidence 1.05 vs 1.00; aHR 1.02, 95% CI 0.70 to 1.49, p=0.93), myocardial infarction (incidence 0.67 vs 0.72; aHR 0.98, 95% CI 0.61 to 1.57, p=0.94), major and clinically relevant non-major bleeding (incidence 4.51 vs 4.34; aHR 0.95, 95% CI 0.79 to 1.15, p=0.63) or heart failure hospitalisation (incidence 3.28 vs 3.07; aHR 1.06, 95% CI 0.85 to 1.32, p=0.60). Conclusion: In this large study of patients with established AF, women had a lower risk of death than men, but there were no sex-specific differences in other adverse outcomes.